Antioxidant and Emulsifying Properties of Modified Sunflower Lecithin by Fractionation with Ethanol-Water Mixtures - Cabezas, Dario Marcelino (2013)
Lecithins are a mixture of acetone insoluble phospholipids, containing mainly phosphatidylcholine (PC), phosphatidylethanolamine (PE), phosphatidylinositol (PI), phosphatidic acid (PA), and other minor substances such as carbohydrates and triglycerides [1-3]. The production of sunflower oil in Argentina, is of utmost importance from an economic point of view [4]. In this country, sunflower lecithin could represent an alternative to soybean lecithin because it is considered a non-GMO product, which is in accordance with the preference of some consumers